Inside BAR (The Biblical archaeology review, 1979)
David Ussishkin is the author of this month’s cover story, "Answers at Lachish." In this important and full-scale report, Ussishkin, as Director of the Lachish Excavations Project, lays out the archaeological history of the site and comes up with crucial new conclusions about which strata on the tell should be associated with the Assyrian […]